2022
DOI: 10.1111/exsy.12982
|View full text |Cite
|
Sign up to set email alerts
|

Self‐adaptive‐deer hunting optimization‐based optimal weighted features and hybrid classifier for automated disease detection in plant leaves

Abstract: This main intention of this paper is to adopt a new disease detection model for plant leaves. The proposed model involves several steps such as pre‐processing, leaf segmentation, abnormality segmentation, feature extraction and detection. Image scaling and contrast enhancement are performed during the pre‐processing phase. Once the pre‐processing is done, the segmentation phase starts with leaf segmentation by binary thresholding method and abnormality segmentation by K‐means clustering. Further, the local bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…In the literature, studies have been carried out on the classification of plant leaves with different colors, textures, veins and sizes. For example, Negi et al [19] tried to detect leaf diseases using the leaves of nine different plants such as Apple, Corn, Grape, and the leaves of ten different plants such as Sahu and Minz [26], Apple, Pepper and Tomato. Since the physical properties of the leaves used in this and similar studies are very different from each other, disease detection is easier than plants with the same physical properties [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature, studies have been carried out on the classification of plant leaves with different colors, textures, veins and sizes. For example, Negi et al [19] tried to detect leaf diseases using the leaves of nine different plants such as Apple, Corn, Grape, and the leaves of ten different plants such as Sahu and Minz [26], Apple, Pepper and Tomato. Since the physical properties of the leaves used in this and similar studies are very different from each other, disease detection is easier than plants with the same physical properties [25].…”
Section: Discussionmentioning
confidence: 99%
“…In the study using CNN architecture, ten diseases were classified with a 96.02% success rate. In another study conducted for ten plants, the classification of healthy and diseased leaves was made by the Sahu and Minz [26]. In the literature, it has been observed that two methods are generally used in studies on the classification of plant diseases.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The features used in this field, such as atmospheric, vegetation, or topological variables, can be analysed using DL techniques. These techniques can extract information from samples faster and more efficiently than humans for specific tasks [15], and their effectiveness can be observed in other problems related to ecology [16][17][18] and the environment [19].…”
Section: Related Workmentioning
confidence: 99%